Szpital wojewódzki w Zielonej Górze w latach 1975-1990 = Regional hospital in Zielona Góra in the years from 1975 until 1990 - Skobelski, Robert (1968- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the period from 1975 until 1990 the hospital in Zielona Góra operated as the Regional Complex Hospital comprising not only the hospital itself, but many other health care service facilities as well (outpatients? clinics, health care centres etc.). The institution at the time consisted of 22 wards with places for 1000 in-patients and employed over 100 staff members, the majority of whom had completed specialist medical training.
Keywords: czasopismo; czasopismo akademickie; Ziemie Zachodnie; stosunki polsko-niemieckie; pogranicze polsko-niemieckie; historia